[PP.07.30] AMBULATORY PULSE WAVE VELOCITY AND AUGMENTATION INDEX PREDICT CARDIOVASCULAR EVENTS AND ALL-CAUSE MORTALITY BETTER THAN OFFICE AND AMBULATORY BLOOD PRESSURE IN HEMODIALYSIS PATIENT. (September 2017) - Sarafidis, P.A.; Liakopoulos, V.; Loutradis, C.; Karpetas, A.; Piperidou, A.; Koutroumpas, G.; Raptis, V.; Syrgkanis, C.; Efstratiadis, G.; London, G.; Zoccali, C.
Abstract : Objective: Patients with end-stage renal disease have extremely high rates of cardiovascular events and mortality. Arterial stiffness and augmentation of the aortic blood pressure (BP) component measured in office conditions are known cardiovascular risk factors in hemodialysis patients. This study examines the prognostic significance of ambulatory brachial and central BP, ambulatory pulse wave velocity (PWV), and ambulatory heart-rate-adjusted augmentation index (AIx75) in this population. Design and method: In this prospective cohort study, 170 hemodialysis patients underwent 48-hour ambulatory monitoring with Mobil-O-Graph NG device during a standard inter-dialytic interval and followed-up for a mean of 28.1 ± 11.2 months. The end-points studied were: (i) all-cause mortality; (ii) cardiovascular death (fatal myocardial infarction, fatal stroke or sudden death); (iii) a combined outcome of cardiovascular death, non-fatal myocardial infarction and non-fatal stroke; (iv) a combined outcome of cardiovascular death, non-fatal myocardial infarction, non-fatal stroke, resuscitation after cardiac arrest, coronary revascularization or hospitalization for heart failure. Results: During follow-up, 37 (21.8%) patients died and 46 (27.1%) had a cardiovascular event or died from cardiovascular causes. Cumulative survival was not different for quartiles of pre-dialysis SBP, 48-hour peripheral SBP, central SBP and central PP, but was progressively shorter with higher ambulatory PWV [95.3%, 85.7%, 61.9% and 69.8% for quartiles 1 to 4 (logrank p < 0.001)] and AIx75 (90.7%, 78.6%, 73.8%. and 69.8% for quartiles 1 to 4 (logrank p = 0.013)]. Similarly, the Hazard Ratios for cardiovascular mortality, for cardiovascular death, or non-fatal MI, or non-fatal stroke, as well as the combined outcome of cardiovascular events were similar for quartiles of predialysis SBP, 48-hour peripheral SBP and 48-hour central SBP, but were progressively increasing with higher quartiles of ambulatory PWV and ambulatory AIx75. In multivariate Cox-regression analysis 48h-ambulatory-PWV was the only vascular parameter independently associated with mortality (HR: 1.604, 95%CI: 1.141–2.255; per m/s increase). Conclusions: Ambulatory PWV and ambulatory AIx75 are independently associated with the risk of cardiovascular events and mortality in this hemodialysis population, whereas office and ambulatory BP are not. These findings add to the evidence suggesting that arterial stiffness is probably the most prominent cardiovascular risk factor in hemodialysis.